2016
DOI: 10.1152/physiolgenomics.00010.2016
|View full text |Cite
|
Sign up to set email alerts
|

Tenotomy immobilization as a model to investigate skeletal muscle fibrosis (with emphasis on Secreted frizzled-related protein 2)

Abstract: The pathological endpoint of congenital and senile myopathies is chronic muscle degeneration characterized by the atrophy of contractile elements, accompanied by fibrosis and fatty infiltration of the interstitium. Tenotomy is the release of preload that causes abrupt shortening of the muscle and models atrophy and fibrosis without prominent inflammatory response. Fibrosis in the skeletal muscle is known to be triggered by transforming growth factor (TGF)-β, which is activated by inflammatory events. As these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 54 publications
(61 reference statements)
1
10
0
Order By: Relevance
“…It was likely responsible, at least part, for the mechanism by which PQQ alleviated skeletal muscle atrophy, mitigated mitophagy and inhibited slow-to-fast muscle fiber type transition induced by denervation. TGF-β1 could induce skeletal muscle atrophy through activating Smad3, and inactivation of Smad3 could reverse the atrophic effect induced by TGF-β (33,34). The activation of TGF-β signaling pathway is also crucial for autophagy, and it could activate autophagy of human hepatic carcinoma HepG2 cells (68).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was likely responsible, at least part, for the mechanism by which PQQ alleviated skeletal muscle atrophy, mitigated mitophagy and inhibited slow-to-fast muscle fiber type transition induced by denervation. TGF-β1 could induce skeletal muscle atrophy through activating Smad3, and inactivation of Smad3 could reverse the atrophic effect induced by TGF-β (33,34). The activation of TGF-β signaling pathway is also crucial for autophagy, and it could activate autophagy of human hepatic carcinoma HepG2 cells (68).…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β1 is a multifunctional cytokine involving in the activation of satellite cells, the formation of connective tissue and the regulation of immune response intensity (32). In skeletal muscle, TGF-β1 could induce skeletal muscle atrophy, requiring Smad3 and JNK activation, and inhibition of Smad3 and JNK1/2 activation could reverse the atrophic effect of TGF-β (33,34). TGF-β1 and p-Smad3 showed significantly increase in murine model of amyotrophic lateral sclerosis, and targeting TGF-β signaling pathway might be a therapeutic approach to improve muscle function in several degenerative diseases (35).…”
Section: Introductionmentioning
confidence: 99%
“…Tenotomy, resection of muscle tendon, activates interstitial fibrosis (Akpulat et al, 2016, Valencia et al, 2017 due to increased levels of MMP-2, TIMP-2, and TGF-β1 (Hirunsai et al, 2015).…”
Section: Surgical-induced Modelsmentioning
confidence: 99%
“…However, this model lacks myofiber necrosis, inflammatory events, and regenerating myofibers (Akpulat et al, 2016). In addition, tenotomy induces myofiber atrophy which results in loss of the contractile function of muscle (Valencia et al, 2017).…”
Section: Surgical-induced Modelsmentioning
confidence: 99%
“…The muscle force decrease in reference to the speed of contraction [ 21 ] and the rise of fatigability [ 22 ] has been quantified. Changes have been primarily explained by a global neuromuscular degeneration [ 23 ], atrophy or slow-to-fast fiber switching [ 20 ], sarcomeric or costameric modifications [ 21 , 23 , 24 ], overproduction of no contractile proteins, such as collagen leading to fibrosis [ 25 ], and occasionally apoptosis [ 26 ]. Vernikos and Schneider reported that exposure to microgravity environments can induce neuromuscular atrophy compared to age-induced atrophy, albeit with a possible reversibility [ 2 ].…”
Section: The Plasticity Of Musclementioning
confidence: 99%